Motion-Cyclo-oxygenase-2 Selective Nonsteroidal Anti-Inflammatory Drugs are as Safe as Placebo for the Stomach: Arguments for the Motion - Richard H Hunt (Canadian Journal of Gastroenterology)
Traditional nonsteroidal anti-inflammatory drugs (NSAIDs) are known to cause gastritis, gastric and duodenal ulcers, and gastrointestinal (GI) blood loss, as well as alterations in small bowel permeability. Patients at a high risk for these complications include those who are older than 60 years of age, those with a previous history of complicated peptic disease and bleeding, and those who take high dose or multiple NSAIDs, including low dose aspirin, corticosteroids or anticoagulants. The introduction of selective inhibitors of cyclo-oxygenase-2 (COX-2) has provided effective treatment of inflammatory arthritis and musculoskeletal pain, with dramatic reductions in the risk of GI adverse events. The two most widely prescribed coxibs are celecoxib and rofecoxib, and others are being developed. Endoscopic studies have revealed that coxibs are only half as likely to induce upper GI ulceration than are traditional NSAIDs, and are as safe as placebo. Furthermore, the newer drugs do not cause excessive blood loss from the GI tract and do not affect small bowel permeability. The Vioxx Gastrointestinal Outcomes Research Study (VIGOR) revealed that the incidence of myocardial infarction was significantly lower with naproxen than rofecoxib, although this study was not designed to look at this endpoint. Coxibs are an important addition to the pharmacotherapy of inflammatory disease.